2020
DOI: 10.1111/joes.12382
|View full text |Cite
|
Sign up to set email alerts
|

Universal Preschool Programs and Long‐term Child Outcomes: A Systematic Review

Abstract: What are the long-term effects of universal preschool programs on child outcomes? We review 26 studies using natural experiments to estimate the effects of universal preschool programs for children aged 0-6 years on child outcomes measured from third grade to adulthood. Studies comparing universal preschool with a mix of parental, family, and private modes of care show mixed effects on test scores and on measures related to health, well-being, and behavior. All estimates for outcomes related to adequate primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 89 publications
3
24
0
4
Order By: Relevance
“…The policy relevance of our study is clear since our results imply that children with disabilities experience unequal access to information and school resources. Research has shown that preschool attendance is positively related to an individual's years of schooling and highest grade completed (Dietrichson, Kristiansen, and Nielsen 2018). Furthermore, preschool attendance is also positively related to an individual's employment and earnings as an adult (Dietrichson, Kristiansen, and Nielsen 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The policy relevance of our study is clear since our results imply that children with disabilities experience unequal access to information and school resources. Research has shown that preschool attendance is positively related to an individual's years of schooling and highest grade completed (Dietrichson, Kristiansen, and Nielsen 2018). Furthermore, preschool attendance is also positively related to an individual's employment and earnings as an adult (Dietrichson, Kristiansen, and Nielsen 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that preschool attendance is positively related to an individual's years of schooling and highest grade completed (Dietrichson, Kristiansen, and Nielsen 2018). Furthermore, preschool attendance is also positively related to an individual's employment and earnings as an adult (Dietrichson, Kristiansen, and Nielsen 2018). Also, if children with disabilities are discriminated against when they apply for school placements, this may increase school segregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also shown that preschool attendance is positively related to an individual's years of schooling and highest educational degree completed later in life. Furthermore, it is also positively related to an individual's employment and earnings as an adult (Dietrichson, Kristiansen, and Nielsen 2018) and to health (Aalto et al 2019). Finally, research indicates that preschool attendance seem to be an efficient way to improve language knowledge among children of immigrants (Drange 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In light of this evidence, many policy makers have strived towards the universalization of preschool (Dietrichson et al, 2020;Gamboa and Krüger, 2016). However, ensuring quality is highly important for the success of these programmes.…”
Section: Child-care Quality and Organizationmentioning
confidence: 99%